Slavery in the Pentateuch and Its Relevance to Human Trafficking in Asia: A Theological Review - Ragil Kristiawan; Sungduk Yun (Predica Verbum: Jurnal Teologi dan Misi, 2026)
Human trafficking in Asia has reached an alarming level, with victims trapped in forced labor, sex trafficking, forced marriage, and other forms of exploitation. Meanwhile, the Pentateuch is often misunderstood as legitimizing slavery, whereas its laws actually contain principles of liberation and protection for the oppressed. This study aims to analyze the concept of slavery in the Pentateuch (Ex. 21, Lev. 25, Deut. 15) and to establish its relevance to the phenomenon of human trafficking in Asia, as well as to formulate theological implications for the Church's response. Using qualitative library research with a descriptive-analytical approach and liberation hermeneutics, this study finds that the slave laws in the Pentateuch emphasize the limitation of slavery periods, protection for escaped slaves, restoration through the Year of Jubilee, and voluntary service based on love. These principles are highly relevant for addressing the root causes of human trafficking, such as poverty, corruption, and weak policies. This study concludes that the Church in Asia is called to be an agent of liberation, providing protection, advocacy, holistic recovery, and preventive education for victims and vulnerable communities.